A heparin derivatives library constructed by chemical modification and enzymatic depolymerization for exploitation of non-anticoagulant functions. (1st December 2020) - Ji, Yang; Wang, Yi; Zeng, Wen; Mei, Xiang; Du, Shanshan; Yan, Yishu; Hao, Jie; Zhang, Zhenqing; Lu, Yuan; Zhang, Chong; Ge, Jun; Xing, Xin-Hui
Highlights: Enzymatic depolymerization kinetics of chemically-modified heparin was analyzed. Low molecular weight chemically-modified heparins were prepared and characterized. The order of chemical modification and HepI lysis affected the product MW distribution. LMW partially 6- O -/ N -desulfated heparin suppressed bleomycin-induced cell apoptosis. Abstract: Non-anticoagulant biological functions of heparin-based drugs have drawn increasing attention. However, the exploration into the non-anticoagulant activities of various low molecular weight heparins was associated with bleeding risks in clinical practice and often led to controversial conclusions due to the structural differences. In this study, we aimed to establish a process to produce a library of heparin derivatives with structural diversity and reduced/abolished anticoagulant activity through the combination of chemical modifications and enzymatic cleavage of heparins. The depolymerization characteristics of various selectively modified heparin derivatives by three heparinases were comprehensively analyzed. The order of periodate treatment and heparinase-I depolymerization was proved to significantly change the structural characteristics of the oligosaccharide products. Finally, among several heparin derivatives that screened in the bleomycin-induced cell apoptosis model, the low molecular weight partially 6- O- / N -desulfated heparins showed the strongest anti-apoptotic activities. This study provided a useful approach for future development of novel heparin-derivative medications.